Makna “Sakral” Dalam Tradisi Budaya Jawa - Suyanto Suyanto (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2018)
This article discusses the meaning of the term "sacred" in Javanese cultural traditions. Understanding the meaning of the term is considered important in the current era, because many people still do not understand it. The impact is that the possibility of the emergence of pros and cons among certain parties to the understanding of ritual culture carried out by certain communities is very possible. The purpose of this article is to try to explore and re-interpret the nature of "sacred", so that in turn it can provide the proper understanding to the community. "sacred" is not merely sacred and wingit. It is more than that. "Sacred" is a process of understanding life in relation to the Creator, which is essentially able to change human attitudes and behavior to be better because it undergoes a process of purification to be free from the darkness and a proof of oneness with the Creator. Keywords: sacred, ritual, meaning, Javanese culture